Peran Dialog Konseling Dalam Mengatasi Minat Beajar Siswa Yang Rendah Di Sekolah - Muh Yusnisam; Fitriyanti Sulaiman; Muhammad Junaedi Mahyuddin (EduPsyCouns: Journal of Education, Psychology and Counseling, 2022)
Abstract: The Role of Counseling Dialogue in Overcoming Low Student Interest in SMP Negeri 2 Enrekang Regency”. The purpose of this article is: To find out how the role of the Counseling Dialogue in overcoming students' low interest in learning at SMP Negeri 2 Enrekang. The type of data in this study is descriptive qualitative data type. This research was conducted at SMP Negeri 2 Enrekang. The subjects in this article are teachers and students at SMP Negeri 2 Enrekang. The data collection techniques used are: Interview, Documentation, Observation and Literature Study. Data analysis in this study used 3 stages, namely: data reduction, data display, verification and conclusion.,The results showed that 1). The role of the Counseling Dialogue to increase student interest in learning at SMP Negeri 2 Enrekang is low. The implementation of the counseling dialogue at the SMP is going well and is in accordance with what was programmed. The programs implemented in conducting guidance and counseling activities consist of: Types of programs, compiling programs, planning activities, carrying out activities, supervising activities, implementing activities and evaluating activities. 2) Supporting and inhibiting factors of Counseling Dialogue in increasing student interest in learning low in middle school. school gives motivation, spirit, to learn to be better. Abstrak: Peran Dialog Konseling Dalam Mengatasi Minat Belajar Siswa yang Rendah di SMP Negeri 2 Kabupaten Enrekang”. Tujuan dari artikel ini adalah: Untuk mengetahui bagaimana peranan Dialog Konseling dalam mengatasi minat belajar Siswa yang rendah pada SMP Negeri 2 Enrekang. Jenis data dalam penelitian ini adalah jenis data deskriptif kualitatif, Penelitian ini dilakukan di SMP Negeri 2 Enrekang. Sebagai Subjek dalam artikel ini adalah guru dan siswa di SMP Negeri 2 Enrekang. Teknik pengumpulan data yang digunakan adalah: Wawncara, Dokumentasi, Observasi dan Studi literatur. Analisa data dalam penelitian ini menggunakan 3 tahapan, yaitu: reduksi data, display data, verifikasi dan kesimpulan. Hasil penelitian menunjukan bahwa 1). peranan Dialog Konseling untuk meningkatkan minat belajar Siswa yang rendah pada SMP Negeri 2 Enrekang adalah Pelaksanaan dialog konseling di SMP tersebut berjalan dengan baik dan sudah sesuai dengan yang diprogramkan. Adapun program yang dilaksanakan dalam melakukan kegiatan bimbingan dan konseling, yakni terdiri dari: Jenis program, menyusun program, merencanakan kegiatan, melaksanakan kegiatan, mengawasi kegiatan, pelaksana kegiatan dan penilaian kegiatan.2) faktor pendukung dan penghambat Dialog Konseling dalam meningkatkan minat belajar siswa yang rendah pada SMP tersebut. sekolah memberi motivasi, spirit, untuk belajar menjadi lebih baik.